Effects of Medical Diagnostic Low-dose X Rays on Human Lymphocytes: Mitochondrial Membrane Potential, Apoptosis and Cell Cycle - Montree Tungjai (2018)
© 2017 Lippincott Williams & Wilkins. Low-dose radiation is widely used across the world for the diagnosis of many diseases by means of a variety of imaging technologies. However, the harmful effects of exposure to low-dose radiation during medical examination remain controversial. The authors studied the effects of medical diagnostic low-dose x rays (i.e., 0.03, 0.05, or 0.1 mGy) after an in vitro exposure of human lymphocytes. Cells with no irradiation served as the non-irradiated control group. Three biological indicators were used to determine the effects of medical diagnostic low-dose x rays at 4, 8, 24, 48, and 72 h post-irradiation. These biological endpoints were mitochondrial membrane potential (ΔΨm), cell cycle, and apoptosis. Results indicated no changes in the ΔΨm, number of apoptotic cells, and cell cycle in lymphocytes exposed to these low doses of radiation, as compared to the corresponding non-irradiated lymphocytes at all harvest time-points. These results suggested that there were no harmful effects of the diagnostic low-dose x rays when human lymphocytes were exposed in an in vitro condition.